Research recast(ed): S2E4 - Hip hop and the Urdu Ghazal, with Sara Grewal - Ekelund, Brittany; Cave, Dylan; Grewal, Sara (My University, 2022)
Today we sat down with Dr. Sara Grewal, to learn about the Urdu ghazal, the politics of hip hop and the importance of language. You can find Sara on Instagram and Twitter at @litmasterg. You can also learn more about her community work by visiting the Punjabi Community Health Services website. This episode is packed with extra to explore, like Ghazals you can check out by Parveen Shakir, Jagjit, and Nusrat Fateh Ali Khan. Sara also shares a bit of a hip hop song with a poignant message, so if you’d like to hear the whole thing go here: https://www.youtube.com/watch?v=ub4jPZzSBe0.
Keywords: poetry; hip hop